The analysis of translation of live metaphors in Japanese novel Haru No Yuki / Melati Desa - Desa, Melati (Universiti Teknologi MARA, 2020)
Language and culture influences each other and its effect is reflected in not only the way humans think, but could also be seen in a full load of figurative elements in creative writing, such as metaphors. Thus, the report examines the aspects of the transfer of meaning in the live metaphors in Haru No Yuki, literary Japanese texts written by Yukio Mishima (1925 – 1970) translated to Malay by Muhammad Haji Salleh (1993) as Salju Musim Bunga published by Penataran Ilmu. This report studies on the equivalence of the meaning of translated live metaphors from the source text to the target text. From the study of the equivalence of meaning can be evaluated that, if there is any type of losses of meaning in form of under translation, over translation or wrong translation. The retention of live metaphors in the target text produced an ideal translation. Universal live metaphors maintained by the translator, this approach produced an ideal translation in form of meaning and accepted by the culture and speakers of the target language. The conclusion of this report shows that, one of the factors in producing quality translations is to understand the elements of the original cultural metaphors contained in the source text.